Efficacy of alternative and biological inseticides on Sitophilus zeamais (Coleoptera: Curculionidae) in corn kernels (Research, Society and Development, 2023)
The study aimed to evaluate the efficiency of alternative and biological insecticides on the population of Sitophilus zeamais in maize grains. The research was conducted in a completely randomized design, containing five treatments, diatomaceous earth (750 g/t), neem oil (10 ml/L), Beauveria bassiana (20 g/L) and tobacco (10 ml/L), and nine repetitions, with each trial comprising 20 adults. For the evaluation of the insecticide activity, samples of corn grains were placed in plastic pots submitted to the treatments. The insecticides were sprinkled and sprayed on the corn grains and later, each sample was infested with 20 unsexed adults of Sitophilus zeamais, aged between 10 and 15 days. Insect mortality was evaluated at 48, 96, 144 and 240 h after application. Total insect mortality was corrected by the Schneider Orelli formula. Afterwards, the data were submitted to the non-parametric Kruskal-Wallis test at a significance level of 5%. If there were significant differences between treatments, the medians were compared by Dunn's test at 5% probability of error. Only the diatomaceous earth insecticide had a significant effect on the mortality of Sitophilus zeamais for the third day (5.56%) and sixth day (84.21%) of product exposure. Neem, tobacco and Beauveria bassiana treatments did not interfere with insect mortality, not statistically different from the control in any of the evaluation dates. The diatomaceous earth product showed greater efficiency on Sitophilus zeamais, reaching a percentage of 89.77% of mortality on the insects.